Compliance and accountability-seeking: Evidence from a field experiment in Argentina - Krakowski, Krzysztof (2025)
Does compliance with low-cost civic duties increase accountability-seeking behaviors among citizenry? We address this question by conducting a field experiment at train stations in Buenos Aires. We create exogenous variation in compliance with paying the public transportation fare by: (i) highlighting sanctions for non-compliance and ii) appealing to social norms whereby 90% passengers pay the ticket. We find that both sanctions and norms treatments raise compliance. However, only appeals to social norms make treated passengers more willing to sign a petition demanding quality public transportation service—our measure of accountability-seeking behavior. To probe the mechanisms explaining these patterns, we show that compliance invoked by adherence to norms makes subjects feel more entitled to demand accountability and trust the government to a greater extent. Our findings suggest that raising compliance through appeals to social norms may thus have wider benefits for civic behaviors.